PENTINGNYA KECERDASAN MUSIKAL PADA ANAK USIA DINI - Anne Febryane Effendi Anne; Resa Respati; Elan (Jurnal Genta Mulia, 2024)
Musical intelligence in early childhood has become a major concern in the field of education and childdevelopment. This research aims to examine in depth the importance of musical intelligence in the earlystages of child development using a literature review method. Through analysis of various relevantliterature sources, this research discusses the main aspects related to musical intelligence in earlychildhood, including its impact on children's cognitive, emotional and social development. The resultsof the literature review show that musical intelligence in early childhood has a significant contributionto the development of various cognitive abilities, such as creative thinking, memory and problem solving.Apart from that, musical activities at an early age also play an important role in improving children's social skills, such as cooperation, communication and appreciation of differences. This research alsoidentified several factors that influence the development of musical intelligence in early childhood,including family environment, interaction with music teachers or instructors, and exposure to varioustypes of music. The implication of these findings is the need to emphasize integrated musical educationin the early childhood education curriculum, as well as the important role of parents and teachers infacilitating the development of children's musical intelligence.